Genetic transformation in Musa species (Banana) - Sagi, L.; Remy, S.; Verelst, B.; Swennen, Rony L.; Panis, Bartholomeus (1995)
The term banana is meant throughout this chapter to cover dessert and cooking bananas as well as plantains. With an estimated total production of more than 76 million tons in 1992 (FAO 1993), banana is the no. 1 fruit crop in the world. Ninety-nine percent of world's annual production is cultivated in more than 110 developing countries. Approximately 90% of the total production is used for domestic consumption: banana is staple food for at least 400 million people. The remaining 10% product entering the world trade market still has a value of 3 billion US$ and serves as dessert for many more millions of people. Therefore, the banana export industry is an important factor for the economies of developing countries in Latin America and more recently in several Asian and African countries.